Native Cultivable Bacteria from the Blueberry Microbiome as Novel Potential Biocontrol Agents - Chacón, Florencia Isabel; Sineli, Pedro Eugenio; Mansilla, Flavia Ivana; Pereyra, Martina Maria; Diaz, Mariana Andrea; Volentini, Sabrina Inés; Poehlein, Anja; Meinhardt, Friedhelm; Daniel, Rolf; Dib, Julián Rafael (Microorganisms (Basel), 2022)
Blueberry production is affected by fungal postharvest pathogens, including Botrytis cinerea and Alternaria alternata, the causative agents of gray mold disease and Alternaria rot, respectively. Biocontrol agents adapted to blueberries and local environments are not known to date. Here, we report on the search for and the identification of cultivable blueberry epiphytic bacteria with the potential to combat the aforementioned fungi. Native, blueberry-borne bacterial strains were isolated from a plantation in Tucumán, Argentina and classified based on 16S rRNA gene sequences. Antagonistic activities directed at B. cinerea and A. alternata were studied in vitro and in vivo. The 22 bacterial strains obtained could be attributed to eleven different genera: Rosenbergiella, Fictibacillus, Bacillus, Pseudomonas, Microbacterium, Asaia, Acinetobacter, Curtobacterium, Serratia, Sphingomonas and Xylophilus. Three strains displaying antagonistic impacts on the fungal pathogens were identified as Bacillus velezensis (BA3 and BA4) and Asaia spathodeae (BMEF1). These strains are candidates for biological control agents of local blueberry production and might provide a basis for the development of eco-friendly, sustainable alternatives to synthetic pesticides.